Tile effect of L-carnitine additions on performance and carcass characteristics of growing-finishing swine - Owen, K.Q.; Weeden, T.L.; Nelssen, Jim L.; Goodband, Robert D. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
An experiment was conducted to evaluate the efficacy of dietary carnitine on growth performance and carcass characteristics of growing-finishing swine. The trial was designed to investigate the response of pigs fed carnitine from weaning to market vs control pigs receiving no carnitine. In addition, the performance of these pigs was compared to that of pigs fed carnitine only during the starter or finishing phases. The trial was broken down into the following four phases: 1) phase I (0 to 14 d post weaning) 2) phase II (14 to 35 d post weaning) 3) grower (d 35 to 135 lb), and 4) finisher (135 to 230 lb). One hundred and twenty-eight pigs averaging 11.40 lb were used in the first two phases to investigate the effects of added carnitine on the performance of the early weaned pig. This also assisted in finding the proper carnitine administration period to elicit optimum growth performance and carcass characteristics in growing-finshing pigs. During phases I and II, one half of the pigs received a high nutrient density diet (HNDD) containing 1000 and 500 ppm, respectively, of carnitine; the other half received a HNDD with no added carnitine. These HNDD were formulated to contain 1.45% and 1.25% lysine, respectively. Pigs were allotted to pens on the basis of weight and sex, with each pen being randomly assigned to treatment. There was a total of 32 pens each containing four barrows or four gilts per pen. During phase I, pigs consuming the diet with carnitine were more efficient and had slightly higher daily gains. Nevertheless, during phase II, pigs receiving no carnitine had higher daily gains. Over the frrst 35 d of the trial, pigs offered no carnitine had higher daily gains and daily feed consumptions but were slightly less efficient. After the first two phases, pigs were reallotted within treatments on the basis of weight resulting in one of the following carnitine treatments: 1) feeding carnitine from weaning to market (15 to 230 lbs); (C/C) 2) carnitine during phases I and II only (C/N), 3) carnitine during growing-finishing only (N/C), and 4) no added carnitine (N/N). A total of 95 pigs (three pigs/pen) were used to provide eight replicates/treatment (four replicates/sex). Grower diets contained .85% lysine, and as pigs approached 135 lb, the lysine content was reduced to .75%. Carnitine was supplemented in the growing-finishing diets (N/C and C/C) at 25 ppm. During the growing-fmishing phase, there were no difference in performance among treatments. However, a significant increase occurred in longissimus muscle area of pigs receiving carnitine only during the growingfinishing phase as compared to pigs fed no additions of carnitine throughout the trial. This suggests that carnitine supplementation during the growing-fmishing phase increases loineye area, but has no effect on growth performance.
Keywords: Swine; L-Carnitine; Growth; Carcass; Starter; G-F